A Study Of Sensitivity Of Bank In Malaysia - Ang, Yueh Sin (2008)
This study is attempted to provide an empirical explore on the sensitivity of bank in Malaysia. Banks are an important sector in Malaysia where their main function is to provide money supply-demand and market.